Caesarean Section as A Prevention of Intrapartum Transmission in Pregnant Woman with Syphilis: A: Case Report - Chandni P. Daryanani; Aloysius Suryawan; Theresia Monica Rahardjo; Apriani Lam; Maxzillion Sky Kasnadi; Nadya Ariella; Stefanie Sumartono; Syifa Navisah (Medical Clinical Update, 2023)
Syphilis is an infectious disease caused by spirochete bacterium Treponema pallidum. Most of the new case of syphilis occur in men, but there is a tendency of increasing infection rate in reproductive-aged women, with the highest rates observed in 20-24 years old. Syphilis can be transmitted by sexual intercourse, blood products transfusion, or transplacental known as congenital syphilis and during delivery process as intrapartum transmission. Syphilis is a relapsing and remitting disease with early and late stages. Congenital syphilis is caused by foetal infection of Treponema pallidum, transmission mostly occurs transplacental, and it may occur at any time during gestation.